PERBEDAAN HASIL BELAJAR EKONOMI SISWA YANG MENGGUNAKAN MODEL COOPERATIF LEARNING TEKNIK TALKING CHIPS (KANCING GEMERINCING) DENGAN PEMBELAJARAN KONVENSIONAL PADA SISWA KELAS X SMA N 1 RANAH PESISIR - Indriani, Roza; , M.Pd, Armiati; M.Pd, Sumarni, (Pendidikan Ekonomi, 2014)
Abstract                 This research was motivated by the results of studying economics class X SMA N 1 Ranah Pesisir is still low, still centered learning to teachers, so that students are less active, creative and motivated. One attempt to improve student learning outcomes is by applying economic models Talking Chips learning techniques. This study to determine the differences in students learning outcomes using economic models Talking Chips learning technique with conventional learning in class X SMA N 1 Ranah Pesisirs. This study is the type of experiment. The study population is a  X grade students of  SMA Negeri 1 Ranah Pesisir, while the sample is X5 class learning model that uses the technique as a class experiment Talking Chips and X4 class as class control with conventional learning. Instrument used was a written test in the form of an objective matter. Data were analyzed by descriptive and inductive analysis through Z. Based on the test results of the test scores of students studying Economics, the average grade obtained by the experiment is 82.23 with a standard deviation of 12.52 and an average grade of control was 75.68 with a standard deviation of 11,60. From the analysis of the Z test is obtained Zhitung (2.782) > Ztabel (1.960) which means H0 is rejected and H1 is accepted . Thus it can be concluded that there are significant differences in learning outcomes of students who use the economic model of learning techniques Talking Chips with conventional learning class X SMA N 1 Ranah Pesisir of the school year 2013/2014.